Effects of converting secondary forest to oil palm plantation on peat soil carbon and nitrogen and other soil chemical properties - Muniandy, Makilan; Ahmed, Osumanu Haruna; Nik Ab. Majid, Nik Muhamad; Yusop, Mohd Khanif (Science Publications, 2009)
Problem statement: Peatlands are natural sequesters of carbon and nitrogen. Once they are disturbed the tendency to lose carbon and nitrogen to the environment is very high. This study investigated the effect of converting peat land forest into oil palm plantation on soil chemical properties with particular emphasis on carbon and nitrogen storage. Approach: Soil samples were collected randomly at depths 0-25 and 25-50 cm from a secondary forest and from four different ages of oil palm plantations at woodman oil palm plantation located in Sarawak, Malaysia. Soil pH in water and KCl, Organic Matter (OM), Organic Carbon (OC), Total Nitrogen (TN), Organic Nitrogen (ON), ammonium, nitrate, available phosphorous, carbon to nitrogen ratio, carbon to phosphorous ratio and bulk density were determined using standard procedures. The bulk density method was used to quantify Carbon (C), Nitrogen (N), ammonium, nitrate and available phosphorous storage on per hectare basis. Results: Statistical analysis showed that the OC content was statistically similar for all soil depths and vegetation types (forest or plantation). The TN content was statistically higher for secondary forest. Conclusion: Regardless of depth, C sequestration was not altered due to land use change but the secondary forest had higher stores of soil N.